Upaya Meningkatkan Minat Belajar PKN Materi Persatuan dan Kesatuan Melalui Model Pembelajaran Problem Based Learning (PBL) pada Siswa Kelas V SDIT Ulil Albab - Dwi Laili Kirana Putri; Nanda Amelia; Farhan Amnan Mullisi; Agung Setyawan (Departement of Mathematics Education, 2023)
Civics subjects are subjects that cannot be separated from our lives, starting from Pancasila values, character education, and unity and oneness. Civics subjects are usually taught by lecture and discussion methods with the same material at each grade level, so that it looks more monotonous and boring for students. The lack of interest in student learning in Civics subjects is a common thing to happen so that learning is often not conducive. On this occasion, researchers used a problem-based learning model. The aim is to increase students' interest in learning Civics subjects for fifth grade students at SDIT Ulil Albab through presenting various problems that exist in the surrounding environment. This type of research is classroom action research using descriptive quantitative methods. The results of the pre-research, cycle I, and cycle II showed an increase from beginning to end. At the beginning of the pre-research the presentation of student interest in learning was only 73.50%, then the researchers carried out further research in cycle I so that the percentage of student interest in learning increased by 14.25% from before, namely to 87.75%. After that the researchers carried out cycle II so that there was an increase in the percentage of interest in learning by 0.49% from cycle I, namely to 88.24%. So that the final conclusion of this study is that there was an increase of 14.74% from the pre-study to cycle II.